ANALISIS PERLAKUAN AKUNTANSI ASET TETAP BERDASARKAN PSAK NO.16 TAHUN 2012 PADA USAHA JASA MULIA GAMES LUBUKLINGGAU - Dewi Anggraini (Jurnal Media Ekonomi (JURMEK), 2016)
Fixed assets are one of the main parts of the company's wealth which are large in number and experience depreciation in one accounting period. In maximizing the role of fixed assets, appropriate policies are needed in the management of fixed assets. The policy for managing fixed assets must be based on PSAK No. 16 of 2012 so that information regarding fixed assets is in accordance with Financial Accounting Standards and can provide good information for decision makers. Mulia Games Lubuklinggau is a company engaged in services that provides entertainment for the community. The data analysis technique used is quantitative analysis which uses a formula for calculating numbers in order to analyze the data obtained and compares the treatment applied by companies with generally accepted Financial Accounting Standards. The results showed that the treatment of fixed assets in terms of recognition of the acquisition of fixed assets, acquisition of fixed assets, expenditure after acquisition of fixed assets, and the elimination of fixed assets in accordance with PSAK No. 16 of 2012, but in terms of depreciation of fixed assets and presentation in financial statements , the company has not treated it in accordance with PSAK No. 16 of 2012 and in its discussion the researcher calculates the depreciation of the company's fixed assets and examines how the company treats its fixed assets.